Lady Rachel Russell "One of the Best of Women" - Schwoerer, Lois G. (Johns Hopkins University Press, 2019)
Originally published in 1987. Lady Rachel Russell (1637-1723) was regarded as "one of the best women" by many of the most powerful people of her time. Wife of Lord William Russell, the prominent Whig opponent of King Charles II who was executed for treason in 1683, Lady Russell emerged as a political figure in her own right during the Glorious Revolution and throughout her forty-year widowhood. Award-winning historian Lois G. Schwoerer has written a biography that illuminates both the political life and the lives of women in late Stuart England. Lady Russell's interest in politics and religion blossomed during her marriage to Lord Russell and after his death: "as William became a Whig martyr, Rachel became a Whig saint." Her wealth, contacts, and role as her husband's surrogate gave her considerable influence to intercede in high government appointments, lend support in elections, and exchange favors with her friend Mary of Orange. In her domestic life she similarly took steps usually reserved to men, managing large estates in London and Hampshire and negotiating favorable marriage contracts for each of her three children. Although Lady Russell was unusual for her time, she was by no means unique. Other notable women shared her concerns and traits, although to differing degrees and effects. Schwoerer suggests that the horizons of women's lives in the seventeenth century may have extended farther than is often supposed.